Aqueous extracts of Moringa oleifera and Cinnamomum cassia as promising sources of antibiofilm compounds against mucoid and small colony variants of Pseudomonas aeruginosa and Staphylococcus aureus - Eduarda Silva; Pedro Ferreira-Santos; José A. Teixeira; Maria Olivia Pereira; Cristina M.R. Rocha; Ana Margarida Sousa (Biofilm)
Bacterial biofilms formed by Staphylococcus aureus and Pseudomonas aeruginosa pose significant challenges in treating cystic fibrosis (CF) airway infections due to their resistance to antibiotics. New therapeutic approaches are urgently needed to treat these chronic infections. This study aimed to investigate the antibiofilm potential of various plant extracts, specifically targeting mucoid and small colony variants of P. aeruginosa and S. aureus and strains. Moreover, it aimed to gain insights into the mechanisms of action and the potential phytochemicals responsible for antibiofilm activity. Solid-liquid extractions were performed on seven biomasses using water and ethanol (70 and 96 %) under controlled conditions, resulting in 21 distinct plant extracts. These extracts were evaluated for extraction yield, antioxidant activity, phenolic content, chemical composition by HPLC-TOF-MS, and antibiofilm activity using a 96-well plate assay, followed by crystal violet staining, bacterial adhesion assessment, and brightfield microscopy. Our findings revealed that aqueous extracts exhibited the highest inhibition of biofilm formation, with cinnamon bark and moringa seeds showing strong antibiofilm activity against both bacterial species. Brightfield microscopy confirmed that these extracts effectively inhibited biofilm formation. Chemical analysis identified key bioactive compounds, including moringin, benzaldehyde, coumarin, and quinic acid, which likely contribute to the observed antibiofilm effects. Recognizing that the antibiofilm properties of moringin, a common compound in both moringa seed and cinnamon bark extracts, remain underexplored, we conducted potential target identification via PharmMapper and molecular docking analyses to provide a foundation for future research. Computational analyses indicated that moringin might inhibit aspartate-semialdehyde dehydrogenase in P. aeruginosa and potentially interact with an unknown target in S. aureus. In conclusion, moringa seed and cinnamon bark extracts demonstrated significant potential for developing new therapies targeting biofilm-associated infections in CF. Further studies are needed to validate the computational predictions, identify the bacterial targets, and elucidate the precise mechanisms behind moringin's antibiofilm activity, which is likely the potential key contributor to the observed activity of the moringa and cinnamon bark extracts.